PENGARUH MOTIVASI DAN KOMPETENSI TERHADAP PRODUKTIVITAS KERJA PEGAWAI PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SAROLANGUN - Mubarrok, Husni; Rasid, Fahmi; Wahyudi, Heri (Sosio Akademika, 2024)
The research entitled the influence of motivation and competence on the work productivity of employees at the Population and Civil Registration Service of Sarolangun Regency which analyzes the influence of motivation and competence on the work productivity of employees of the Population and Civil Registration Service of Sarolangun Regency uses descriptive statistical analysis methods and verification analysis in the form of partial least squares (PLS) and SPSS 21. Research results where motivation directly has a significant effect on employee productivity, where the t statistical value (6.080) is greater than the t-table (2.006). Then the competency variable directly has a significant effect on employee productivity, where the statistical t value (2.450) is greater than the t-table (2.006). The results of this research have implications for efforts to increase employee work motivation in each work unit so that it will have an impact on increasing employee productivity.